2023
DOI: 10.4149/neo_2023_220823n857
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0002938 (circCRIM1) promotes the progression of esophageal squamous cell carcinoma by upregulating transcription factor 12

Abstract: Growing evidence has indicated that circular RNAs (circRNAs) play crucial roles in the tumorigenesis and progression of diverse malignancies. However, the majority of circRNAs involved in esophageal squamous cell carcinoma (ESCC) remain undefined and the exact functions and underlying mechanisms of circRNAs in ESCC still need further exploration. In this study, we identified a novel onco-circRNA hsa_circ_0002938, derived from the exons of cysteine-rich transmembrane BMP regulator 1 (CRIM1) pre-mRNA, referred t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Next, we explored the specific molecular mechanism of circCRIM1 in CIR. Studies have confirmed that circCRIM1 can function as a ceRNA to bind to miRNAs in different diseases 26,27 . Thus, we studied whether circCRIM1 exert the ceRNA function in CIR.…”
Section: Resultsmentioning
confidence: 92%
“…Next, we explored the specific molecular mechanism of circCRIM1 in CIR. Studies have confirmed that circCRIM1 can function as a ceRNA to bind to miRNAs in different diseases 26,27 . Thus, we studied whether circCRIM1 exert the ceRNA function in CIR.…”
Section: Resultsmentioning
confidence: 92%